2010
DOI: 10.1007/s12192-009-0161-6
|View full text |Cite
|
Sign up to set email alerts
|

HLA complex-linked heat shock protein genes and childhood acute lymphoblastic leukemia susceptibility

Abstract: Three heat shock protein 70 (HSP70) genes, HSPA1L, HSPA1A, and HSPA1B, are located within the human leukocyte antigen (HLA) class III region. HSPs act as stress signals and regulate natural killer cell response to cancer. HSP70 gene polymorphisms show disease associations partly due to their linkage disequilibrium with HLA alleles. To systematically evaluate their associations with childhood acute lymphoblastic leukemia (ALL), we examined the three functional single nucleotide polymorphisms (SNPs) rs2227956 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…These youngest infants may be more susceptible to the development of acute leukemia in utero, because specific HLA-DRB and HLA-DRQ haplotypes have been associated with different forms of leukemia and may be linked to polymorphisms in heat-shock protein genes (HSPA1A and HSPA1B) located in the HLA class III region. 41,44 Polymorphisms of HSPA1A, HSPA1B, and other inflammatory or immunomodulatory genes, such as IL-8 or VCAN, also have been reported to influence susceptibility to cancer. 45,46 In conclusion, we have developed gene expression classifiers that improve outcome prediction in infant ALL, beyond the well-established prognostic factors of patient age and MLL gene rearrangement status.…”
Section: Discussionmentioning
confidence: 99%
“…These youngest infants may be more susceptible to the development of acute leukemia in utero, because specific HLA-DRB and HLA-DRQ haplotypes have been associated with different forms of leukemia and may be linked to polymorphisms in heat-shock protein genes (HSPA1A and HSPA1B) located in the HLA class III region. 41,44 Polymorphisms of HSPA1A, HSPA1B, and other inflammatory or immunomodulatory genes, such as IL-8 or VCAN, also have been reported to influence susceptibility to cancer. 45,46 In conclusion, we have developed gene expression classifiers that improve outcome prediction in infant ALL, beyond the well-established prognostic factors of patient age and MLL gene rearrangement status.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs in non-coding regions can regulate the binding activity of transcriptional factors by altering the structure of some transcriptional domain binding sites (Jeng et al, 2008;Shibata et al, 2009;Ucisik-Akkaya et al, 2010). Using statistical analysis, Mukai et al (2005) found that SNP in the 5'-untranslated region of the CD40 gene had some influence on its expression, and Ordovás et al (2008) found the g.763G>C SNP in the 5'-untranslated region of the bovine FASN gene affects its promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed previously [55], the two approaches should be viewed as complementary strategies for identification of disease associated loci as they both have their respective strengths and weaknesses depending on the study being conducted. A review of the literature identified six xMHC childhood ALL candidate gene studies of non-classical HLA loci, and statistically significant associations have been reported for SNPs of the HFE , HSPA1B and BAT3 genes [56,57,58]. None of the SNPs specifically examined in these studies were genotyped as part of the current mapping panel which precluded our ability to directly evaluate these previous associations.…”
Section: Discussionmentioning
confidence: 99%